Environmental Security Revisited - Read, Mark (Scientia Militaria - South African Journal of Military Studies, 2024)
The concept “environmental security” grew out of the environmental movement of the 1970s, gaining significant attention in the academic and policy communities at the end of the Cold War in the early 1990s. Early writings focused mainly on how security-related activities, including armed conflict, affect the environment, and how environmental issues might influence or drive national or international security. By the early 2000s, numerous perspectives and definitions of environmental security had evolved, and were being debated in scholarly literature, including more subtle ways by which environmental change might influence security. Some scholars contested the very concept of environmental security. By the 2010s, research and writing focused on environmental security diminished, to some extent being replaced by discussions and debates in both academic and policy settings about the relationship between climate change and security (later referred to by some as “climate security”). In recent years, conversations about environmental security are re-emerging, driven in part by an acknowledgment that the overriding focus on climate change security might be too narrow, missing other ways that environmental change influences security, and vice versa. The study on which this article reports, briefly traced the history of environmental security in both academic and policy literature. Next, the article summarises climate change security perspectives, discussing the climate–conflict nexus, and including examples of climate security strategy and policy. The article then explains aspects of environmental security that are excluded or neglected from the climate security discourse, making a case for a return to a more expansive approach to environmental security. Finally, an updated definition of and framework for environmental security are proposed. Environmental security is seen as the ability of individuals, groups, or states to adapt to, mitigate, or avoid environmental change without critical adverse effects, which significantly degrade the integrity, values, or well-being of states, communities, or individuals. The definition incorporates elements of the original, state-focused definition of environmental security, but also includes important elements of human security (that affect community or state security).